Application of New Blended Catalyst for Synthesizing of Fluoro Intermediate in Herbicide Industries - AHMADI, A. (Asian Journal of Chemistry, 2010)
Difluoropyridines generally have high thermal stability and are useful agricultural chemicals particularly as pre-emergence herbicides where they are effective in controlling a variety of noxious weeds. For instance, 5-chloro-2,3-difluoro pyridine, can be used for the preparation of pyridinyloxyphenoxy alkane carboxylic acid derivatives, which are herbicides with particularly advantageous properties. This compound was synthesized with higher yield in comparison with previous methods, by using new technique and blended catalysts in two blended polar aprotic solvents. After synthesizing, the product was separated from the reaction mixture, by slow fractional distillation with heat sealed cover and vigorous column. This compound is an important starting material for the preparation of agrochemicals and pharmaceuticals compounds.